The influence of teachings of publicists on the development of international law - Sivakumaran, Sandesh (Cambridge University Press, 2017)
This article considers the influence of teachings of publicists on the development of international law. The category of ‘teachings of publicists’ is not a homogeneous one. The article argues that it can be divided into: entities that have been empowered by States to conclude teachings, such as the International Law Commission; expert groups, such as the Institut de Droit International; and ‘ordinary’ publicists. The teachings of ordinary publicists are also of different types and include digests, treatises, textbooks, monographs, journal articles, and blog posts. Only by breaking down the category into its various types can the influence of the teaching of publicists on the development of international law be properly gauged. Even then, it can prove rather difficult to pin down the notion of ‘influence’. Standard assessments of influence focus on the extent to which teachings are cited by courts and tribunals, in particular by the International Court of Justice. However, that approach privileges the role of courts and tribunals in the development of international law and overlooks the role of other actors. As such, the present article offers a different assessment of influence. It identifies the actors that comprise the community of international lawyers and analyses the various interactions that take place between these actors and the teachings of publicists. It is through this interaction, of which citation is but part, that the influence of the teachings of publicists can properly be determined.